Wspólna Polityka Rolna Unii Europejskiej a funkcjonowanie rolno-spożywczego rynku hurtowego w Polsce - Noga, Beniamin (The Common Agriculture Policy in the EU and Wholesale Markets in Poland, 2008)
This article analyzes the possibilities of development of agricultural wholesale market in Poland after the country's accession to the European Union. The Common Agricultural Policy (CAP) creates the new reality for the Polish agricultural market and particularly for the sales system of agricultural products. As a result of the implementation of CAP, the Polish wholesale market has gained significant importance.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 165-172